2019
DOI: 10.1111/jerd.12520
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender and clinical experience on shade perception

Abstract: Objective Shade matching is a critical procedure in prosthetic dentistry. The correct identification of the shade by the doctor as well as the perception of the shade by the dental technician becomes critical due to the high patient expectations. The current study aims to evaluate the effect of gender and clinical experience on shade perception by dental professionals. Materials and Methods A total of 100 dental professionals with normal color vision who were categorized as dental students, dental doctors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
(65 reference statements)
2
21
1
3
Order By: Relevance
“…The frequencies calculated are tabulated and depicted in (Table 1 and Table 2) .Chi square test was done between age group and colour match. Results showed statistically significant differences in shade matching among the groups,(P<.0.001).with very good and good shade matching being the most predominant ones (Figure 1 ).The results obtained states that the shade match is highly achieved and it consensus with the study by 16,26,7 which states that the shade match in the age group has high satisfactory population with very low crevice in shade match of the fixed partial dentures.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The frequencies calculated are tabulated and depicted in (Table 1 and Table 2) .Chi square test was done between age group and colour match. Results showed statistically significant differences in shade matching among the groups,(P<.0.001).with very good and good shade matching being the most predominant ones (Figure 1 ).The results obtained states that the shade match is highly achieved and it consensus with the study by 16,26,7 which states that the shade match in the age group has high satisfactory population with very low crevice in shade match of the fixed partial dentures.…”
Section: Resultssupporting
confidence: 54%
“…1,2 .The aesthetic success is dependent upon the close shade matching between the dental restoration and the adjacent teeth 3,4 .The shade matching is done to adapt restoration with the surrounding tissues 5,6,7,8 . The demanding aspect within the aesthetic dentistry is regarding the duplication and characterisation of colour 5,9,10 .The shade perception is psychophysiological response it is regulated by the human eyes and sensory structures of brain towards the reflection of light spectrum from any object 2,11,12 .Some elements give direct demand and impact on the colour of a restoration 13,14 .The common elements that gives impact includes lightning conditions, thickness of porcelain, soft tissue colour, core material, soft tissue shade selection system, firing process and fabrication 15,16,17 . The judgement made on shade selection has some factors that include ambient light, surrounding colour, clothes, makeup of the patient and chromatic perception of the dentist 18,19,20 .These factors results in frequent errors while performing shade selection 21,22 There are various approaches in shade selection method which is used for aesthetic success in shade match 23,24 .The study was to determine shade matching in fixed partial denture patients 25,26…”
Section: Introductionmentioning
confidence: 99%
“…39 However, several studies found no significant differences in the shade matching results between men and women. 11,40 Therefore, five men and four women (aged 20-25 years) participated in our study as examiners, and we did not find any differences in shade matching reliability between genders. Age may also influence tooth shade determination ability.…”
Section: Discussionmentioning
confidence: 82%
“…All the other 33 studies specified the source as daylight, artificial light, or a combination of these two (Table 2 details light parameters of individual studies). There were 4 studies that used daylight as the single source of light, of which 1 reported significantly better female performance, 54 while 1 found no significant difference 1,32,33 . Artificial light was the main light source in 23 studies.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Improper shade selection is a frequent reason for refabrication of dental restorations. 1,5 Proper color matching based on the surrounding teeth is thus a critical, yet highly challenging, task for the dentist or dental technician. The commonly used international standards for color research in dentistry are defined by the International Organization for Standardization and Commission Internationale de l'Eclairage.…”
Section: Introductionmentioning
confidence: 99%